Investigating foundations for hominin fire exploitation: Savanna-dwelling chimpanzees (Pan troglodytes verus) in fire-altered landscapes. Issue 167 (June 2022) - Herzog, Nicole M.; Pruetz, Jill D.; Hawkes, Kristen
Abstract: Humans' extensive use of fire is one behavior that sets us apart from all other animals. However, our ancestors' reliance on controlled forms of fire—i.e., for cooking—was likely preceded by a long familiarity with fire beginning with passive exploitation of naturally burned landscapes and followed by intermediate steps including active ecological modification via intentional burning. Here we explore our pyrophilic beginnings using observational data from savanna-dwelling chimpanzees. These data highlight the extent to which anthropogenic burning impacts the behavior and ecology of sympatric primates and provides an opportunity to study the ways in which apes living in a fire-altered world exploit opportunities presented by burning. Using monthly burn scar data and daily range use data we quantify the impact of burning episodes on chimpanzee habitat. Over the course of one dry season, approximately 74% of the total estimated range of the Fongoli community of savanna-dwelling chimpanzees ( Pan troglodytes verus ) was impacted by fire. We combine fire occurrences with behavioral data to test for relationships between burning and rate of encounter with food items and duration of subsequent patch residence time. Results show more frequent encounters and shorter patch residence times in burned areas. These data can be leveraged as a frame of reference for conceptualizing our extinct relatives' behavior around fire. Highlights: Quantifies impact of anthropogenic and natural fire on savanna ape foraging ecology. Burned areas are associated with improved foraging opportunities. Results help illuminate a conceptual framework for hominins' route to pyrophilia.